How to read literature like a professor : a lively and entertaining guide to reading between the lines - Foster, Thomas C (New York : Harper Perennial, 2014)
A thoroughly revised and updated edition of Thomas C. Foster's classic guide--a lively and entertaining introduction to literature and literary basics, including symbols, themes, and contexts--that shows you how to make your everyday reading experience more rewarding and enjoyable. While many books can be enjoyed for their basic stories, there are often deeper literary meanings interwoven in these texts. How to Read Literature Like a Professor helps us to discover those hidden truths by looking at literature with the eyes--and the literary codes--of the ultimate professional reader: the college professor. What does it mean when a literary hero travels along a dusty road? When he hands a drink to his companion? When he's drenched in a sudden rain shower? Ranging from major themes to literary models, narrative devices, and form, Thomas C. Foster provides us with a broad overview of literature--a world where a road leads to a quest, a shared meal may signify a communion, and rain, whether cleansing or destructive, is never just a shower--and shows us how to make our reading experience more enriching, satisfying, and fun. This revised edition includes new chapters, a new preface, and a new epilogue, and incorporates updated teaching points that Foster has developed over the past decade
Introduction: how'd he do that? -- Every trip is a quest (except when it's not) -- Nice to eat with you: acts of communion -- Nice to eat you: acts of vampires -- Now, where have I seen her before? -- When in doubt, it's from Shakespeare -- Or the Bible -- Hanseldee and Greteldum -- It's Greek to me -- It's more than just rain or snow -- Never stand next to the hero -- Interlude: does he mean that? -- More than it's gonna hurt you: concerning violence -- Is that a symbol? -- It's all political -- Yes, she's a Christ figure, too -- Flights of fancy -- It's all about sex -- Except sex -- If she comes up, it's Baptism -- Geography matters -- So does season -- Interlude: one story -- Marked for greatness -- He's blind for a reason, you know -- It's never just heart disease and rarely just illness -- Don't read with your eyes -- It's my symbol and I'll cry if I want to -- Is he serious? and other ironies -- A test case -- Postlude: who's in charge here?
Includes index
Includes bibliographical references, filmography, and index
Keywords: Literature -- Explication; Books and reading; Criticism; Literature -- History and criticism; Criticism, interpretation, etc